نظمِ قرآن اور ربط و مناسبت ِ آیات کا تجزیاتی مطالعہ : An analytical study of the Nazm-ul-Qur'ān and the Interconnectedness of the Verses - Kiran, Sadia; Umbreen, Dr. Faryal; Hassan, Mohsan (Al-Amīr Research Journal for Islamic Studies, 2023)
The Qur’ān, the holy book of islam, is revered not only for its spiritual guidance but also for its remarkable coherence and relevance. Throughout its verses, there exists a profound interconnectedness and relevance that transcends time and context. This coherence is often referred to as "rabt" or the intricate web of connections between different parts of the Qur’ān. The Qur’ān itself attests to this interconnectedness, stating, "and those who disbelieve say, 'why was the Qur’ān not revealed to him all at once?' thus [it is] that we may strengthen thereby your heart. And we have spaced it distinctly" (Qur’ān 25:32). This deliberate arrangement serves to reinforce key themes, principles, and narratives, fostering a deeper understanding of divine wisdom and guidance. The significance of this coherence lies in its ability to provide a comprehensive framework for spiritual reflection, moral guidance, and practical application in various aspects of life. It underscores the Quran’s timeless relevance and its capacity to address the complexities of the human condition across different ages and cultures. Keywords: Qur’an, Nazm-ul-Qur’an, Coherence, Interconnectedness, Iʻjāz-ul-Qur’an, Divine Wisdom.